KEPADATAN DAN POLA DISTRIBUSI KIJING (Glauconome virens, LINNAEUS 1767) DI EKOSISTEM MANGROVE BELAWAN - Machrizal, Rusdi; Wahyuningsih, Hesti; Jumilawaty, Erni (Fakultas Perikanan dan Kelautan Universitas Riau, 2014)
The aims of this study were to determine density and distribution pattern of ki-jing (G. virens) in Belawan Mangrove Ecosystem. Sample were collected with a smallsquares 1x1 m 2 as much as 45 with interval 1 m. The results of this study showed thehighest value of the density was found in station III 2.93 Ind /m 2 , while at the station I2.80 Ind / m 2 . The lowest one was found in station II 1.16 Ind / m 2 . Distribution patternof Kijing on station I and II was uniform with id value 0.645 and 0.958, on the contra-vy on station III was clumped with id value 1.421.